The Point of View - James, Henry, 1843-1916 (Salt Lake City, UT : Project Gutenberg, 2001)
"The Point of View" by Henry James is a novel written in the late 19th century. It explores the themes of identity and cultural contrasts through the experiences of two women, Miss Aurora Church and her mother, Mrs. Church, as they journey from Europe to America. The narrative reflects on their perceptions of American society and their own place within it, set against the backdrop of their expatriate experiences and differing attitudes toward their cultural origins. At the start of the book, we are introduced to Aurora Church, who writes a lively letter from a ship, basking in the joys of her journey back to America. She shares her observations about the people on board, her rebellious spirit, and her reflections on her mother$1 (Bs stern demeanor. Aurora is eager for the freedom she anticipates in her homeland, contrasting her independence with her mother's more serious outlook. The opening captures Aurora's playful criticisms of both her fellow passengers and the American cultural landscape she is about to re-encounter, setting the stage for their subsequent challenges as they adjust to their lives in the United States. Through her witty and engaging writing style, James provides a glimpse into the characters' complex emotions and foreshadows the tensions that will arise from their contrasting viewpoints. (This is an automatically generated summary.)s
Release date is 2001-10-01
David Price, Christine Merriman, Judith Lando-Deurvorst and Twister Dragon
Keywords: United States -- Social life and customs -- 19th century -- Fiction; Europeans -- United States -- Fiction; United States -- Description and travel -- Fiction